ANALISIS PRODUKTIVITAS KERJA PEGAWAI DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN LIMA PULUH KOTA PADA MASA PANDEMI COVID-19 - Nopi Rita; Yulihasri Yulihasri (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
This study aims to determine the work productivity of employees during the pandemic Covid-19 the Youth and Sports Tourism Office District of Fifty Cities and to find out the inhibiting factors in influencing employee work productivity during the pandemic Covid-19 at the Youth and Sports Tourism Office District of Fifty Cities. This study used a purposive sampling technique where the researcher selected 9 key informants from different fields and then this research was analyzed by quantitative description. The results showed that employee work productivity during the Covid-19 pandemic at the Fifty Cities District Tourism and Sports Youth and Sports Office decreased. This can be seen from the results of interviews that there is a delay in completing work. There are 4 factors inhibiting work productivity, namely first, weak supervision, second timeliness, third lack of motivation, and and finally limitations in facilities and infrastructure